Sinomenine relieves oxygen and glucose deprivation-induced microglial activation via inhibition of the SP1/miRNA-183-5p/IÎºB-Î± signaling pathway - Qin, Feng; Zhao, Yang; Shang, Wei; Zhao, Zhi"‘Ming; Qian, Xin; Zhang, Bei"‘Bei; Cai, Hui (Cellular and Molecular Biology, 2018)
Studies have shown that the inflammatory activation of miroglia (MG) and nuclear factor kappa B ( NF-ÎºB ) play a dominant role in inflammatory response. Previous studies have shown that sinomenine, an anti-inflammatory agent extracted from Sinomenium acutum, can directly protect neurons against cerebral ischemia injury. However, there are no reports on its effect on ischemia/reperfusion-induced inflammatory activation of MG. In the present study, an in vitro ischemia/reperfusion model was developed with mouse BV-2 microglia cells, a model of oxygen-glucose deprivation/reperfusion (OGD/R), and the inhibitory effect of sinomenine pretreatment on inflammatory activation was confirmed through measurement of inflammatory indicators. Mechanistically, sinomenine suppressed OGD/R-induced inflammatory activation through the SP1/miRNA-183-5p/IÎºB-Î± pathway. In conclusion, this study shows that sinomenine effectively inhibits OGD/R-induced inflammatory activation in MG by suppressing the activation of transcription specificity protein 1 (SP 1). This finding is of significance for the clinical use of sinomenine in treating cerebral ischemia/reperfusion injury.